The Effects of sowing date and plant density on seed and flower yield of Pot Marigold (Calendula officinalis L.) - MJ Seghatoleslami; gr Mousavi (فیزیولوژی محیطی گیاهی, 2008)
Medicinal herbs have been used to promote health for centuries, and have increased in popularity and sales in the last 10-20 years. Pot marigold (Calendula officinalis L.) is a medicinal herb whose dried flower heads are used to heal wounds. In order to understand the effects of sowing dates and plant density on grain and flower yield of pot marigold, an experiment was conducted at Agricultural Research Center of Islamic Azad University, Birjand Branch in 2005. Three sowing dates (30 March, 14 April and 30 April) and three plant densities (plant distances on row were 10, 20 and 30 centimeters) were compared in a split- plot design based on randomized complete blocks with 3 replications. Seed and flower yield were significantly different at planting dates and plant densities. Sowing date had significant effects on flower and seed harvest index. The latest sowing date had the highest flower and seed harvest index. Plant density did not have any significant effect on flower harvest index, but the effect on seed harvest index, was significant. In total, the result showed that the first sowing date with 25plants/m2 had the highest grain and flower yield.